Loadability curves for the new Terna's "5F" high capacity overhead lines - Guarniere, M. R.; Palone, F.; Spezie, R.; Buono, L.; Papi, L.; Tresso, G.; Lauria, S.; Maccioni, M. (2023 IEEE International Conference on Environment and Electrical Engineering and 2023 IEEE Industrial and Commercial Power Systems Europe (EEEIC / I&CPS Europe), 2023)
Terna, the Italian Transmission System Operator, has recently introduced a new generation of HV and EHV lines (the so-called "5-phases" or 5F) allowing for a substantial reduction of EMF population exposure and increase of power transfer capacity, if compared to conventional OHL. Due to the reduced visual impact and EMF 5F lines can thus be an effective and efficient solution for the refurbishment of existing ac backbones. The paper presents a loadability study of 5F configuration for several standard voltages in Europe (150 kV, 230 kV and 400 kV) as well as higher voltages, usually adopted for long distance transmission (i.e. 735 kV). Results show that the novel line configuration, when applied to the 400 and 735 kV levels, can transfer up to 3200 MW at 400 kV over a 400 km distance and up to 6 000 MW at 735 kV over 1000 km distance, respectively, subject to conservative angle displacement and voltage drop limits.